Women Scholars in Hong Kong In Pursuit of Intellectual Leadership - Ruan, Nian. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book depicts the diverse approaches of established women professors in perceiving and developing intellectual leadership in Hong Kong. It analyzes the combined influences of various disciplines, different higher education institutions, and gender on the careers of female scholars in the East Asian region. The complexity and interaction of academic careers for women, disciplinary contexts, higher education systems, and socio-cultural environments may present a relatively holistic landscape for readers interested in academic life and leadership. Scholars, administrators, managers, and policymakers in higher education-related fields may gain comprehensive ideas to facilitate faculty and institutional development through a cultural and sociological lens. This may empower female academics and students, while also providing benefits for doctoral students and early-career researchers seeking insights into the evolving advantages and disadvantages in women's academic careers. Audiencesinterested in gender issues may find it intriguing to compare women scholars with women in other professions and in different cultural contexts.
Introduction -- Literature Review -- The Theoretical Framework -- Research Design and Methodology -- Strategic Gamers -- Persistent Navigators -- Unconventional Fighters -- Opportunistic Achievers -- Discussion and Conclusion. .
Keywords: Education, Higher; Psychology, Industrial; Leadership; Feminism; Feminist theory; Higher Education; Leadership Psychology; Feminism and Feminist Theory